Asesmen Potensi Energi Angin Menggunakan Metode Weibull dalam Perencanaan Pembangkit Listrik Tenaga Bayu di Kabupaten Gorontalo, Provinsi Gorontalo - Aswin, Aswin; Pakpahan, Sarinah; Fauziah, Siti (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2025)
This study presents a rigorous assessment of wind energy potential in Gorontalo Regency, Indonesia, through statistical modeling utilizing the two-parameter Weibull distribution applied to hourly wind speed data from 2022 to 2024 across three geographic zones and three elevation levels (50 m, 80 m, 100 m). The model exhibited strong statistical agreement with observed data, evidenced by high variation (R² > 0.9869) and low RMSE values (< 0.011), confirming its robustness in capturing wind behavior. Mean wind speeds, along with key Weibull-derived metrics—most probable wind speed (vmp) and wind speed for maximum energy contribution (vme)—showed a positive correlation with altitude, where zone 1 recorded the highest vme at 7.45 m/s at 100 m. Derived power density values indicated that Zones 1 and 3 fall within the